Multi-species biofilm of Candida albicans and non-Candida albicans Candida species on acrylic substrate - Apurva K Pathak; Sanjay Sharma; Pallavi Shrivastva (Journal of Applied Oral Science, 2012)
OBJECTIVE: In polymicrobial biofilms bacteria extensively interact with Candida species, but the interaction among the different species of the Candida is yet to be completely evaluated. In the present study, the difference in biofilm formation ability of clinical isolates of four species of Candida in both single-species and multi-species combinations on the surface of dental acrylic resin strips was evaluated. MATERIAL AND METHODS: The species of Candida, isolated from multiple species oral candidiasis of the neutropenic patients, were used for the experiment. Organisms were cultured on Sabouraud dextrose broth with 8% glucose (SDB). Biofilm production on the acrylic resins strips was determined by crystal violet assay. Student's t-test and ANOVA were used to compare in vitro biofilm formation for the individual species of Candida and its different multi-species combinations. RESULTS: In the present study, differences between the mean values of the biofilm-forming ability of individual species (C. glabrata>C. krusei>C. tropicalis>C. albicans) and in its multi-species' combinations (the highest for C. albicans with C. glabrata and the lowest for all the four species combination) were reported. CONCLUSIONS: The findings of this study showed that biofilm-forming ability was found greater for non-Candida albicans Candida species (NCAC) than for C. albicans species with intra-species variation. Presence of C. albicans in multi-species biofilms increased, whereas; C. tropicalis decreased the biofilm production with all other NCAC species.